Scalar Products in Twisted XXX Spin Chain. Determinant Representation - Belliard, S.; Slavnov, N.A. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
We consider the XXX spin-1/2 Heisenberg chain with non-diagonal boundary conditions. We obtain a compact determinant representation for the scalar product of on-shell and off-shell Bethe vectors. In the particular case when both Bethe vectors are on shell, we obtain a determinant representation for the norm of the on-shell Bethe vector and prove orthogonality of the on-shell vectors corresponding to the different eigenvalues of the transfer matrix.